Prosopanche demogorgoni: a new species of Prosopanche (Aristolochiaceae: Hydnoroideae) from southern Brazil - Funez, Luís Adriano; Ribeiro-Nardes, Weslley; Kossmann, Thiago; Peroni, Nivaldo; Drechsler-Santos, Elisandro Ricardo (Phytotaxa, 2019)
Here we describe a new species of Prosopanche from southern Brazil. This is the first report of Prosopanche in Santa Catarina state and for the Atlantic Forest region. We present field photographs, illustrations, ecologic and conservation comments on the new species. We contrast the morphology of the new species with the other Prosopanche species that occur in Brazil, P. bonacinai and P. caatinguicola. The new species is morphologically similar to P. bonacinai, which has anthers composed by 20–30 thecae, synandrium 15–25 × 6–8 mm and tepals 35–55 × 9–20 mm vs. anthers composed by 3–4 thecae, synandrium 5–6 × 3–4 mm and tepals 15–20 × 5–8 mm in P. demogorgoni.